IMPLEMENTASI EKSTRAKURIKULER KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 1 MARISA - Adam, Meilan; Arif, Muh.; Datunsolang, Rinaldi (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This study aims to determine the forms of religious extracurricular activities in shaping religious character and to determine the challenges of implementing religious extracurricular activities in shaping the religious character of students at SMA Negeri 1 Marisa, in this case religious extracurricular activities are extracurriculars that contain Islamic activities as the development of Islamic Religious Education materials carried out outside school hours. This type of research is descriptive qualitative research. Where the data collected is obtained through primary and secondary data, with data collection techniques using observation and documentation techniques as well as in-depth interviews with informants. Then the data is processed and analyzed using descriptive analysis methods, namely reducing data, presenting data and drawing conclusions related to religious extracurricular activities in shaping the religious character of students at SMA Negeri 1 Marisa. The results of this study show that the form of implementation of character building in students at SMA Negeri 1 Marisa consists of: 1) Sunnah Fasting Monday-Thursday, 2) Dhuha Prayer, Remembrance and Infak, 3) Eradication of Qur'an Illiteracy. The challenges of implementing religious extracurricular activities in shaping religious character are, 1) unsupportive family conditions, 2) influence on students, 3) limited supervision of the school